The affairs of Annabel ; Annabel takes a tour : double feature [videorecording (DVD)] - Ball, Lucille, 1911-1989; Stoloff, Ben, 1895-1960; Oakie, Jack, 1903-1978 (Archive collection., 2016)
Lucille Ball and Jack Oakie team up for a double helping of laughter and fun in this uproarious two-film collection featuring the zany misadventures of screen queen Annabel Allison and her publicist Lanny Morgan. In The Affairs of Annabel (1938); Lanny decides to promote Annabel's upcoming film The Man and the Maid by getting her a job as a servant; but the stunt backfires when gangsters take over the household. Lanny's harebrained schemes continue in the second and final film of the series; Annabel Takes a Tour (1938); where the press agent cooks up a romance between a British viscount (Ralph Forbes) and his client but neglects to tell Annabel it's all a fake and that her new boyfriend is married with children.